Defining Severe and Persistent Mental Illness—A Pragmatic Utility Concept Analysis - Zumstein, Naomi; Riese, Florian (Frontiers in Psychiatry, 2020)
The concept of severe and persistent mental illness (SPMI) lacks a consensual definition. Variations in definitions stem above all from different meanings about the constituent features of the concept and how to operationalize them. Our objective was to clarify the concept of SPMI and to explore the level of concept maturity through pragmatic utility (PU) concept analysis. Our findings suggest that severe and persistent mental illness is a partially mature concept that needs further clarification. We argue that the lack of a uniform definition is inherent to the problem: SPMI refers to a patient population rather than a disease entity, and the term has to be useful for different stakeholder purposes. Therefore, while an agreement on the principle three dimensions included in a definition may be possible (diagnosis, disability, and duration), their operationalization will have to be context-dependent and specific for the task at hand.